AKAD SALAM DAN PROBLEMATIKANYA DI PERBANKAN SYARIAH, PENDEKATAN KRITIS - Jaharuddin Jaharuddin; R Melda Maesarach (Media Ekonomi, 2021)
The purpose of this study is to analyze the application of the salam contract, its development, find problems and provide alternative solutions so that the salam contract can be applied in Indonesian Islamic banking. Research method This research is qualitative research with a critical approach. The results of this study are (1). Salam contract can be applied in Islamic banking in Indonesia and provides benefits as working capital for farmers, fishermen, and MSMEs. Salam contract should be encouraged to be implemented. (2). Salam contract is not implemented in national sharia banking, thus the partiality of sharia banking to farmers, fishermen, and MSMEs, is still not visible. (3). The solution for implementing salam contracts in national Islamic banking is by (a). philosophical re-orientation, namely the re-orientation of the objectives and business model of Islamic banks that are different from conventional banks. (b). Carry out positive law reforms by sharia in Indonesia (shari'a-based omnibus law). (c). Operational technical adjustments, HR literacy, community literacy, and risk management are based on a philosophical re-orientation and strategic reform. And d). The political will of the government, the DPR, and the Indonesian and international community